2022
DOI: 10.1002/ctm2.1056
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1‐phosphate lyase facilitates cancer progression through converting sphingolipids to glycerophospholipids

Abstract: Background In addition to potent agonist properties for sphingosine 1‐phosphate (S1P) receptors, intracellularly, S1P is an intermediate in metabolic conversion pathway from sphingolipids to glycerolysophospholipids (glyceroLPLs). We hypothesized that this S1P metabolism and its products might possess some novel roles in the pathogenesis of cancer, where S1P lyase (SPL) is a key enzyme. Methods The mRNA levels of sphingolipid‐related and other cancer‐related factors were measured in human hepatocellular carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 108 publications
(174 reference statements)
0
14
0
Order By: Relevance
“…In our case, the S1P levels remained unchanged in tissue or cell samples, which is consistent with previous studies ( He et al, 2010 ; Ceccom et al, 2014 ; Couttas et al, 2014 ; Kurano et al, 2022c ), which reported either unchanged or decreased S1P levels and SK activity, suggesting a difficulty to employ S1P receptor agonists. These discrepancies might be attributed to postmortem effects, because S1P can be intracellularly degraded ( Uranbileg et al, 2022 ) or because of the lower accuracy of the comprehensive measuring method in the measurement of S1P versus the specific measuring methods of S1P. In fact, in our previous paper using a specific measuring method of S1P, the brain S1P levels were lower in the AD brains ( Kurano et al, 2022c ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our case, the S1P levels remained unchanged in tissue or cell samples, which is consistent with previous studies ( He et al, 2010 ; Ceccom et al, 2014 ; Couttas et al, 2014 ; Kurano et al, 2022c ), which reported either unchanged or decreased S1P levels and SK activity, suggesting a difficulty to employ S1P receptor agonists. These discrepancies might be attributed to postmortem effects, because S1P can be intracellularly degraded ( Uranbileg et al, 2022 ) or because of the lower accuracy of the comprehensive measuring method in the measurement of S1P versus the specific measuring methods of S1P. In fact, in our previous paper using a specific measuring method of S1P, the brain S1P levels were lower in the AD brains ( Kurano et al, 2022c ).…”
Section: Discussionmentioning
confidence: 94%
“…Sphingolipids are among the well-studied bioactive lipid mediators, playing crucial roles in the physiology and pathology of human diseases ( Kluk and Hla, 2002 ; Hla, 2003 ; Nakamura et al, 2021 ; Kurano et al, 2022a , b , d ; Uranbileg et al, 2022 ). In the field of neurology, their structural role in cellular membranes, particularly in lipid rafts, is a crucial aspect of their interaction with the amyloid beta (Aβ) metabolism ( Olsen and Faergeman, 2017 ), suggesting the potential to investigate their role in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Fumonisin B1 and SKI II were relatively effective in inhibiting cell proliferation in HepG2 and Huh7.5 cells [ 108 ]. S1P lyase facilitates cancer progression by converting S1P into glycerophospholipids [ 57 ].…”
Section: Sphingolipid Metabolic Pathway In Hcc Therapymentioning
confidence: 99%
“…52 Negative associations with both ceramides and sphingomyelins suggest that ceramides are probably diverted to the catabolic pathway to generate more pro-growth signaling molecules. Blocking of key enzymes, such as sphingosine kinase 2 (SphK2) 53 and S1P lyase (SPL) 54 in sphingolipids metabolism, 52 has also been shown to block liver cancer growth in cell and animal bioassays. Our results point to a higher activity of ceramidases in liver that can serve to both promote cell survival and to suppress the ceramide dependent apoptotic cascade.…”
Section: Anti-apoptotic Mechanismsmentioning
confidence: 99%